Partisipasi Masyarakat di Dalam Program Sanitasi Perkotaan Berbasis Masyarakat Studi Kasus : Kelurahan Banyumanik Kota Semarang - Rurin Roesiyana; Wiwik Widayati; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2015)
AbstractBy : RurinRoesyianaNIM : 14010111130088 Department of Government Science Faculty of Social and Political Science Diponegoro University Semarang  In order to accomplish the objectives of MDGs (Millennium Development Goals) which has become paradigm of global development, Indonesian Government has committed to accomplish all the objectives and targets. One of the commitments is reducing the number of residents who is not able to gain access to safe and sustainable clean water source and basic sanitation facilities in 2015. Semarang Municipality has the most community based sanitation program,  75  facilities  in  total.  Banyumanik  Sub-District  is  one  of  the  locations  for  the community based sanitation program.The research was aimed to observe and explain form of community participation in the program of community based sanitation as well as factors influencing the residents to support the program community participation in Banyumanik Sub- District. The method used in the research was descriptive qualitative where facts were described systematically. The data was then analyzed by in-depth interview to the stakeholders and documentation.The research that participation was done by the residents of Banyumanik Sub- District in forms of thoughts, direct participation, and materials. The influencing factors in the community participation are social economy, education, knowledge of program’s objective andbenefits,   local   history,   organizational   influence,   gender   egalitarianism,   and   community awareness to have healthy lifestyle. Key words: Community Participation, Sanitation